Uso de aplicaciones móviles en el proceso de aprendizaje del idioma inglés por parte de los estudiantes de la Carrera de Pedagogía de los Idiomas Nacionales y Extranjeros de la UNACH - Huaraca Roldan, Hernan Kleber (2022)
Mobile learning is one didactic strategy that allows the incorporation of educational technology, so the learner has the opportunity to inspect and make use of their time to achieve innovative knowledge, as it supports formal and informal learning anywhere and anytime. The aim is to determine the use of mobile applications in the process of learning English by students of the Pedagogy of National and Foreign Languages career of the UNACH; the quantitative approach was used as a methodology with a non-experimental-transversal design, descriptive scope, the technique applied was the survey based on a questionnaire that was applied to a sample of 162 students corresponding to the Pedagogy of National and Foreign Languages career of the UNACH. The results obtained that 97% of students have mobile devices and enjoy internet connection within the university campus; 43% spend between 3 and 5 hours a day connected to social networks, and 40% for educational purposes. For this reason, to conclude, most students and teachers use educational apps to facilitate learning the English language. In addition, they affirm that as students, they are constantly using their mobile devices to perform English tasks. Finally, they agree that educational apps do help as learning tools.